Pengaruh Sistem Tirani Dalam Kepemimpinan terhadap Kinerja dan Loyalitas Anggota : Kepercayaan pada Pemimpin Sebagai Variabel Intervening - Irwan Tahir; Suriyanti, Suriyanti; Serlin Serang (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2025)
This study aims to analyze the direct effects of Tyrannical Leadership on Leader Trust, Performance, and Loyalty, as well as evaluate the mediating role of Leader Trust. A quantitative approach was employed, with a population consisting of Polri members and a sample selected through purposive sampling. Data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The findings revealed that Tyrannical Leadership had no significant effect on Leader Trust and Loyalty but had a small significant effect on Performance. In contrast, Leader Trust had a significant and strong influence on both Performance and Loyalty. These results highlight the importance of trust as a key element in enhancing subordinate performance and loyalty, while also demonstrating that tyrannical leadership is less effective in fostering productive working relationships. This study recommends Polri to adopt a trust-based leadership style focused on transparent communication, consistency, and the creation of a fair and supportive work environment